The Identification of Seasonality in the Housing Market Using the X13-ARIMA-SEATS Model - Mach, Łukasz; Dąbrowski, Ireneusz; Wotzka, Daria; Frącz, Paweł (Identyfikacja sezonowości na rynku mieszkaniowym przy użyciu modelu X13-ARIMA-SEATS, 2023)
Aim: In the conducted research, profiles of seasonality in the housing market were determined, which provided an opportunity to answer two fundamental questions: what is the nature of harmonic variation in the seasonality and periodicity of the studied components of the construction process? what parameters of the ARIMA model optimally describe the construction market? Methodology: In the conducted research, using the X13-ARIMA-SEATS model, seasonal decomposition was carried out in the various stages of the housing construction process. Results: The research process conducted to identify seasonal fluctuations in the housing construction market showed that harmonic fluctuation profiles can be identified on an annual basis. An analysis of seasonal fluctuations was carried out for each of the three stages of the housing construction process, while also checking how these profiles function for Poland in general, and for individual investors, and for those building apartments for sale or to rent. The study showed that the market for real estate development activity differs in its seasonal characteristics from that of individual investors. Implications and recommendations: The conclusions obtained from the research can provide support in the decision-making process, both from a macro and microeconomic perspective. Parameterisation of the occurring fluctuations, and taking them into account in the process of developing a forecast can provide decision-making rationale in the implementation of macroprudential and financial stability policies Originality/Value: A novelty is in the demonstration that the residential real estate market in Poland shows different seasonal parameters, divided into the market of individual investors and investors who build apartments for sale or rent.
Econometrics = Ekonometria, 2023, Vol. 27, No. 4, s. 29-43
Keywords: seasonality; real estate market; X13-ARIMA-SEATS; sezonowość; rynek nieruchomości